2016
DOI: 10.1017/s0014479716000545
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Rice Varieties – I. Age of Varieties and Patterns of Variability

Abstract: SUMMARYFarmers who continue to grow old and obsolete varieties do not gain the benefits they could get from growing newer ones. Given the potential large scale of these foregone benefits, relatively few studies have examined the age of varieties that farmers grow. In three surveys, members of over 3300 households were interviewed to find the rice varieties they grew in 2008 and 2011 in 18 districts in the Terai, the low-altitude region of Nepal. This provided the first description of detailed geographical patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Kou et al (2017a) found that EO 3 decreased the N, P and K uptakes of SY63 under the same free-air O 3 enrichment facility, whereas Zhao et al (2015) observed a decrease in N uptake of SY63 rice grown under EO 3 in open-top chambers. The delayed occurrence of the maximum root development (except for root volume) may reflect a maintained rice growth under oxidative stress conditions (Coleman et al, 1996;Witcombe et al, 2017). However, this would also imply that less assimilated C could be used for reproductive growth and grain formation.…”
Section: Discussionmentioning
confidence: 99%
“…Kou et al (2017a) found that EO 3 decreased the N, P and K uptakes of SY63 under the same free-air O 3 enrichment facility, whereas Zhao et al (2015) observed a decrease in N uptake of SY63 rice grown under EO 3 in open-top chambers. The delayed occurrence of the maximum root development (except for root volume) may reflect a maintained rice growth under oxidative stress conditions (Coleman et al, 1996;Witcombe et al, 2017). However, this would also imply that less assimilated C could be used for reproductive growth and grain formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average age of top 5 wheat varieties varied from about 10 years in Punjab to 23 years and 22 years in Madhya Pradesh and Rajasthan, respectively. Witcombe et al (2016) have highlighted that the weighted average age measure underestimates the true age of the varieties that is defined by the year of release. In our study, the average age and weighted average age of the varieties varied significantly only in the case of Punjab and Madhya Pradesh states.…”
Section: Temporal Diversity In Wheat Varieties Cultivated In Indiamentioning
confidence: 99%
“…Dixon et al (2006) have made a similar observation stating that though many smallholders throughout the developing world have benefited from the introduction of first-generation green revolution cultivars that replaced lower-yielding landraces, adoption of second-and third-generation cultivars offering improvements in yield, output quality, and stress resistance seems to be occurring at a much slower pace. Witcombe et al (2016) in their recent study have found that the average age of rice varieties adopted in Nepal was 20 years. The authors remarked that the cultivation of older varieties is a widespread phenomenon in the developing world.…”
Section: Temporal Diversity In Wheat Varieties Cultivated In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly because of the limited availability of local mungbean varieties with high yield potential as well as strong base for disease resistance, which in turn is the result of narrow genetic base of most of the local varieties. As pulses are grown by the farmers with small land-holdings, the only attractive trait of a new commercial variety is the higher grain yield [2,3], and easy availability of such varieties to the farmers ensures harvesting of benefits from these varieties [4,5]. New seed varieties ensure yield enhancement as well as higher per unit land production as compared to the traditional crop varieties [6].…”
Section: Introductionmentioning
confidence: 99%